PSX-21 Influence of estrous synchronization on herd calving distribution and weaning weight. (7th December 2018) - Walker, J; Perry, G; Rich, J; Northrop, E; Perkins, S; Grussing, T; Rusche, W
Abstract: Reproductive efficiency is critical for profitability in cow-calf operations, and age of calf is the largest factor that affects weaning weight. Thus, the objective of this study was to evaluate the use of estrous synchronization and/or AI on calving distribution and weaning weight. Beef heifers and cows (n=962) in 11 herds were randomly assigned to one of three of the following treatments (two treatments/herd): 1) bulls were introduced on day 1 of the breeding season, 2) cows had an intravaginal progesterone device inserted for seven days before bulls were introduced, or 3) cows were synchronized with the 7-d CO-Synch+CIDR protocol and artificially inseminated followed by bull introduction 10 d later. Calving distribution was determined by actual birthdates. A subset of calves were weighed at weaning. Data were analyzed using the GLIMMIX procedure of SAS to test the effects of synchronization and/or AI on calving distribution, average daily gain, and weaning weights. Herd was included as a random variable. Synchronization resulted in more calves born from d 1–10 (P<0.001; 44% vs 24%). Non synchronized cows had a greater (P<0.05) number of calves born between d 11–21 (30% vs 20%) and d 22–42 (30% vs 21%). Overall there was no difference (P=0.95) in the percentage of cows that calved. When adjusted to a common age calf weaning weights were not affected by synchronization (P=0.74) or breeding method (P=0.20). However, AI sired calves had greater ADG compared to natural service (P<0.05; 1.27 ± 0.03 vs 1.23 ± 0.03 kg/d), and male calves were 10 kg heavier at weaning than female calves (P<0.05). In summary, estrous synchronization increased the proportion of cows calving earlier, and when weaning occurs on a common day this will increase pounds of calf weaned. In addition, calves from AI'ed cows had improved ADG.